2016
DOI: 10.1063/1.4952951
|View full text |Cite
|
Sign up to set email alerts
|

Highly strained AlAs-type interfaces in InAs/AlSb heterostructures

Abstract: Spontaneously formed Al-As type interfaces of the InAs/AlSb system grown by molecular beam epitaxy for quantum cascade lasers were investigated by atomic resolution scanning transmission electron microscopy. Experimental strain profiles were compared to those coming from a model structure. High negative out-of-plane strains with the same order of magnitude as perfect Al-As interfaces were observed. The effects of the geometrical phase analysis used for strain determination were evidenced and discussed in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The difference between these two values is smaller than the precision of experimental measures done at interfaces by analyzing atomic resolved (Scanning)-TEM images. 4 Heterostructures with larger or smaller values of m and/or n presented similar results (not shown).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…The difference between these two values is smaller than the precision of experimental measures done at interfaces by analyzing atomic resolved (Scanning)-TEM images. 4 Heterostructures with larger or smaller values of m and/or n presented similar results (not shown).…”
supporting
confidence: 52%
“…Experimentally, spontaneously formed interfaces are not perfect and extend over 2 or 3 monolayers, but they could reach the same level of strain as expected for a perfect tensile Al-As type interface. 4 Using a modified growth procedure, interfaces with a high compressive stress were also achieved. 5 High and localized strains also exist in various mismatched heterostructures, thanks to the same interfacial configuration as here ([InAs/GaSb] 6 and [ZnTe/CdSe] 7 ) or to a nanowire geometry [8][9][10] for instance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, A. Ponchet's group cooperated with Baranov's group to investigate the extent of InAs/AlSb interfaces. They performed strain and elemental analysis by applying atomically resolved Z-contrast images by high-angle annular dark-field imaging in a scanning transmission electron microscope (HAADF-STEM) [7]. They demonstrated a high content of Al-As bonds at the interface.…”
Section: Strain In Inas/alsb Multilayer Structuresmentioning
confidence: 99%
“…As a result, large localized strain may exist at the interfaces; and the strain strongly influence the electronic properties of an InAs/AlSb based QCL. Recent transmission electron microscopy (TEM) studies indicated that Al-As bonds are more favorable at both interfaces, however, the interfacial structures can be complex, extending up to 3 monolayers (ML) [5]- [7]. An illustration of InSb-type and AlAs-type interface is plotted Figure 1.1.…”
Section: Introductionmentioning
confidence: 99%